PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVa SD NEGERI 010 SUNGAI PANJI-PANJI KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Elyana, Riza; Noviana, Eddy; Putra, Zetra Hainul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research with implementation of problem based learning model aimed at students IVa grade of state SD Negeri 010 Sungai Panji-panji Kecamatan Kubu Babussalam that is done in the second semester grade of year of 2014/2015 on January to june 2015, its aims to improve learning outcomes of IPA learning outcomes. The subject were students IVa which is total of 20 students, consisted of 9 boys and 11 girls. The data research shown that either learning process or students achievement increased. It is proved on the teacher and students activities score. Percentage of teacher activities in cycle I that is equal to 60 with good category, while the activities of teachers have the highest average total of 85 with very good category. The cycle I and Cycle II have increased is 25. percentage of students activities had the lowest of first meeting cycle I total of 55% with enough category, the highest average of students activities total of 80 with good category. Meanwhile for first meeting cycle I and Cycle II have increased is 25%. The total of students completed is 9 students or 63,35, from the base score cycle I increased is 75,00 with completed is 16 students, while the cycle II increased is 80,00 with completed is 18 students. So, the difference in increase between base score cycle I is 18,38%, meanwhile the cycle II from base score cycle II increase is 26,28%. So, research with application of problem based learning model have increased IPA learning outcomes of IVa grade of SD Negeri 010 Sungai Panji-Panji Kecamatan Kubu Babussalam.Keywords : problem based learning, IPA learning outcomes